Reduce CO2 Emissions Using Double Skin Façade in Smart & Green Learning Center UGM Promoting Sustainable Building - Murwantoro Panghargiyo; Arif Kusumawanto (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2025)
The Smart & Green Learning Center is a tower building that offers coworking spaces on both its east and west sides. The objective of this study is to explore the impact of a double skin façade on heat generation and CO2 gas emissions in co-working spaces. To achieve this, the IES Virtual Environment software simulation method was employed. The monthly average heat gain without the use of a double skin façade ranged from 19 to 21.9 MWh, while the same metric with a double skin façade was between 14.1 and 16.1 MWh. This resulted in a decrease of 4.9 MWh (25.79%) for the lowest monthly average heat gain and a decrease of 5.8 MWh (26.48%) for the highest. Moreover, the use of a double skin façade led to a reduction in CO2 gas emissions by 20.7% to 21.1% at the Smart & Green Learning Center.